Enhanced recovery and abbreviated length of anticoagulation for thromboprophylaxis after primary hip arthroplasty rationale and design of the ENABLE-hip trial - Drees, Philipp A.; Schmidtmann, Irene; Herbst, Manuel; Becker, Dorothea; Barco, Stefano; Klok, Frederikus A.; Keller, Karsten; Hobohm, Lukas; Christodoulou, Konstantinos C.; Abele, Christina; Bauersachs, Rupert; Ageno, Walter; et al. (Journal of thrombosis and thrombolysis, 2025)
Surgical total hip arthroplasty (THA) is associated with high risk of venous thromboembolism (VTE), but the appropriate duration of postoperative anticoagulation remains controversial. “Enhanced Recovery and Abbreviated Length of Anticoagulation for Thromboprophylaxis After Primary Hip Arthroplasty” (ENABLE-Hip) is a multicenter investigator-initiated and academically sponsored randomized double-blind active-control non-inferiority trial. Patients will be mobilized early after surgery, following a standardized enhanced recovery protocol. After an initial open-label prophylactic anticoagulation as per local standard of care until day 2 after surgery, treatment with rivaroxaban (10 mg once daily) will be started on day 3 and continued until day 10. Subsequently, patients will be switched to placebo in the experimental arm, or continue on active drug in the control arm, until a total of 35 days. The primary endpoint is acute symptomatic or fatal VTE within 3 months. A sample size of 2,932 patients will provide ≥ 80% power to reject the null hypothesis that δ ≥ 0.01 (δ = difference between the two arms in symptomatic VTE probability) at a significance level α = 0.05. An interim analysis will be performed after 3-month follow-up of the first 1,760 randomized patients at a significance level α = 0.50, leading to stop for futility if significance is not obtained, or if recalculation yields a sample size of > 3,200 patients. ENABLE-Hip will be the first major randomized trial to test an overall reduction in the duration of post-THA thromboprophylaxis and will inform future guideline recommendations concerning this continuously growing patient population.
Online veröffentlicht: 29. Mai 2025
Gesehen am 02.09.2025